STRENGTHENING ENGLISH LANGUAGE SKILL: ENGLISH LANGUAGE LEARNING PROGRAMME BASED ON CONTEXTUAL TEACHING AND LEARNING FOR THE YOUNG GENERATION OF TEGAL ISLAND - Andriyaningsih, Ayu; MS, Vike Aprilianin; Sutiyono, Sutiyono (PT. Jurnal Center Indonesia Publisher, 2025)
This community service program aimed to enhance the English language skills of elementary school students on Tegal Island, Lampung Province, through the implementation of a Contextual Teaching and Learning (CTL) approach. Limited English proficiency among local children has long hindered effective communication with foreign visitors and restricted opportunities for community-based tourism development. To address this challenge, the program incorporated basic English vocabulary related to the beach environment into interactive activities, such as songs, games, visual aids, and direct exploration of local surroundings. These methods were designed to provide authentic, engaging, and memorable language learning experiences tailored to the learners’ environment. A pre-test and post-test design was employed to evaluate the program’s effectiveness. The results demonstrated a substantial improvement in students’ vocabulary mastery, with mean scores rising from 61.36 on the pre-test to 89.73 on the post-test. Statistical analysis using a paired sample t-test revealed a significance value of 0.000 (p < 0.05), confirming that CTL significantly enhanced vocabulary acquisition. The normalized gain (N-Gain) indicated a high level of progress among participants, showing consistent improvement across all learners. Beyond cognitive gains, qualitative observations indicated that students exhibited greater confidence, motivation, and environmental awareness as they linked English lessons to familiar contexts. This program illustrates that CTL offers a practical, low-cost, and highly effective strategy for empowering youth in remote island communities. By contextualizing English instruction in real-life settings, CTL not only fosters academic achievement but also supports community engagement, cultural pride, and sustainable human resource development in rural tourism areas.